ENSURING UKRAINE’S FINANCIAL SECURITY IN TIMES OF WAR: DEFENSE PROCUREMENT AND INTERNATIONAL ASSISTANCE - Карапетян, Ольга; Карапетян, Артем; Рудий, Роман (SWorldJournal, 2026)
Ensuring the financial security of Ukraine during wartime is a critically important area of state policy and macroeconomic management, determining the resilience of the economy, the state’s ability to meet its financial obligations, and maintain socio-eco